PROVIDING AND IMPLEMENTATION OF INTERCULTURAL COMMUNICATION IN EUROPEAN DOCUMENTS - Melnyk, Nataliia; Kapeliushna, Tetiana (Studies in Comparative Education, 2020)
The article identifies the features of intercultural communication in the context of European regulations. Based on an analytical review of scientific research of European and domestic scientists, the authors have identified the essence of the concept of "intercultural communication" in the European educational space and European documents in particular; clarification of the difference between the concepts of intercultural and cultural communication. The set of theoretical methods made it possible to identify the leading trends in European policy in the field of intercultural communication, ways to implement the main tasks and provisions of such policy and outline its main priorities and difficulties in modern socio-political conditions characterized by instability and uncertainty. It is established that intercultural communication in the European scientific and educational dimension is understood as a way of cooperation and cultural exchange, which provides for the establishment of understanding between representatives of different countries, nationalities, religions, etc. The priority goals of intercultural communication according to the provisions of European documents in this direction are: to foster intercultural understanding, tolerance, mutual respect and ethics of global citizenship and shared responsibility; development of intercultural empathy and education, training of representatives of different nations, ethnic groups and peoples to consider, analyze and solve problems related to cultural differences; to cultivate in the representatives of different states intercultural attitudes, including the manifestation of tolerance, respect, curiosity and receptivity to other cultures; to ensure the acquisition by representatives of different cultures and states of cultural knowledge, both general and specific to a particular culture, paying special attention to contextual and subtextual cultural elements; to recognize the natural and cultural diversity of the world, to recognize that all cultures and civilizations can contribute to sustainable development and are its decisive factors. Analysis of the functioning of various structural organizations of the EU revealed that their professional and social activities are directed in two directions: conceptual (dissemination of information on new laws and regulations of the European Union in the field of intercultural communication), which ensures the implementation of the value component of intercultural communication; functional (organization of various cultural events, events aimed at cooperation between representatives of different nations, ethnic groups, social strata, etc.), which ensures the implementation of basic tasks by means of direct communication and various forms of intercultural communication (festivals, creative weeks, days of European culture in education and public cultural institutions, thematic exhibitions in museums, various choreographic and theatrical performances for children and adults, etc.). It is determined that the most relevant trends in the development of European educational policy in the field of intercultural communication are: the establishment of broad communication and partnership in various spheres of life, especially - education, culture, politics and economics; expansion of public interaction and partnership for peace with the countries of the Eastern region; search for permanent means of influencing public opinion on the rule of human rights and freedoms in relation to the will, cultural affiliation, recognition and acceptance of intercultural diversity; establishing cooperation between the Ministries of Culture, Education and Science, the Ministries of Foreign Affairs; development of the existing network of cultural, public and public organizations for the dissemination of knowledge and competencies in intercultural communication; further financial assistance and encouragement of exchange between scientific circles and practices in the field of international cultural relations. Among the barriers to the implementation of intercultural communication, the authors distinguish: creating and maintaining a comfortable psychological atmosphere for each representative of different cultures; ensuring tolerant interaction and cooperation; optimal organization of group cooperation and ensuring the implementation of the principle of diversity.